Development Of PMMA Based Polymer Electrolyte For Rechargeable Lithium Batteries - Tan, Chin Guan (2008)
In this research, suitable amount of lithium salt and filler enhances the ionic conductivity of the PMMA-based solid polymer electrolyte which is supported by the EIS, FTIR, XRD adnd SEM characterisations.